Accrual of older adults to cancer clinical trials led by the Canadian cancer trials group – Is trial design a barrier?. Issue 3 (April 2020) - Hernandez-Torres, Catalina; Cheung, Winson Y.; Kong, Shiying; O'Callaghan, Chris J.; Hsu, Tina
Abstract: Background: Older adults (OA), aged 65 years and over, are under-represented in studies. Strict exclusion criteria have been identified as a potential barrier to accrual of OA. This study aims to determine: 1) whether accrual of OA to trials led by the Canadian Cancer Trials Group (CCTG) has increased since 2003; 2) whether exclusion criteria have broadened over time; 3) whether exclusion criteria are associated with lower accrual of OA. Materials and Methods: Phase III and randomized phase II CCTG-led trials initiated from 1990 onwards were included. Trial protocols were reviewed for exclusion criteria. Associations between trial characteristics and percentage of OA accrued were compared using multivariate linear regression modelling. The frequency of exclusion criteria in trials initiated pre- and post-2003 was compared using the Chi-Square test or Fisher exact test. Results: Sixty-nine trials involving 34, 957 patients were included. Accrual of OA to trials remained low compared to OA diagnosed with cancer in Canada (40.8% vs. 56.1%, p < .001). There was a small increase in the accrual of OA since 2003 (42.8% vs. 39.3%, p = .04). There was no relaxation of exclusion criteria over time. Studies initiated prior to 2003, breast cancer studies and studies with exclusion criteria based on renal dysfunction were associated with lower accrual of OA (p < .05). Central nervous system studies were associated with higher accrual of OA (p = .03). Conclusion: OA remain under-represented in trials. While there has been minimal change in exclusion criteria over time, renal dysfunction was the only exclusion criteria associated with lower accrual of OA.